Amorphous carbon encapsulation of metal aerosol nanoparticles for improved collection and prevention of oxidation. Issue 11 (18th September 2013) - Scharmach, William J.; Sharma, Munish K.; Buchner, Raymond D.; Papavassiliou, Vasilis; Vajani, Gaurav N.; Swihart, Mark T.
<x xml:space="preserve">Abstract</x> A technique to encapsulate silver nanoparticles in an amorphous carbon matrix to facilitate nanoparticle collection and limit nanoparticle oxidation is presented. A carbon source added to the metal salt precursor solution decomposes to generate amorphous carbon, which forms large aggregates that are efficiently collected by filtration. The carbon matrix can be removed by oxidation with hydrogen peroxide without damaging the silver nanoparticles within it. X‐ray diffraction showed no evidence of oxidation of encapsulated particles over a two‐week period, whereas bare particles showed oxidation after 1 day. Slight oxidation was observed following carbon removal, but no further oxidation was detected over a subsequent two‐week period. Carbon encapsulation improves nanoparticle collection efficiency, relative to direct collection of unagglomerated silver nanoparticles with membrane filters. The yield of metal nanoparticles is increased by a factor 1.5 to 3 using this approach. The encapsulating carbon itself forms dendritic nanostructures that may also be of interest. © 2013 American Institute of Chemical Engineers AIChE J, 59: 4116–4123, 2013